The design companion for planning and placemaking (RIBA Publishing, 2017)
This book is an essential primer to help those involved in planning secure higher standards of building, open space and neighbourhood design and the delivery of better places. The UK Government's policy for design in the planning system is contained in the National Planning Policy Framework (NPPF), with expanded guidance being provided in the Planning Practice Guidance (PPG). This book expands on these and provides up to date explanations, examples, top tips and practical advice to help the reader understand and apply national design policies and guidance. The book is structured in an easy to use fashion, with general principles and concepts described in Part 1, and Part 2 explaining how these can be applied to particular development types, such as housing, public space or tall buildings.